1998
DOI: 10.1021/ja972633s
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Incorporation and Interfacial Structures in MCM-41 Mesoporous Molecular Sieves

Abstract: Two-dimensional (2D) solid-state NMR spectroscopy has been used to identify interfacial species and establish framework locations of aluminum atoms incorporated in aluminosilicate MCM-41 mesophases and mesoporous solids. In these experiments, chemical shifts of protons in the material are correlated with the chemical shifts of nearby (ca. 1 nm) 13C, 27Al, or 29Si species via their respective heteronuclear dipole−dipole couplings. For aluminosilicate MCM-41 mesophases prepared at room temperature, 2D heteronucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
140
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(153 citation statements)
references
References 65 publications
(218 reference statements)
10
140
1
2
Order By: Relevance
“…Following calcination or solvent extraction to remove the structure-directing block-copolymer species, post-synthesis grafting of aluminosilica moieties onto the interior mesopore walls introduces both hydrophilic and acidic surface properties. [38,39] While mesoporous silica or aluminosilica alone have relatively poor proton conduction properties, [40] incorporation of strong acid moieties, such as perfluorosulfonic acid species, onto their interior mesopore surfaces and channels results in films with high and stable proton conductivities, even at temperatures above 150°C. The preparation of a heterogeneous membrane material that combines high mesoscale ordering, crack-free inorganic film integrity, high hydrophilicity, and high proton conductivity, however, is exceedingly difficult to achieve in a single processing step.…”
mentioning
confidence: 99%
“…Following calcination or solvent extraction to remove the structure-directing block-copolymer species, post-synthesis grafting of aluminosilica moieties onto the interior mesopore walls introduces both hydrophilic and acidic surface properties. [38,39] While mesoporous silica or aluminosilica alone have relatively poor proton conduction properties, [40] incorporation of strong acid moieties, such as perfluorosulfonic acid species, onto their interior mesopore surfaces and channels results in films with high and stable proton conductivities, even at temperatures above 150°C. The preparation of a heterogeneous membrane material that combines high mesoscale ordering, crack-free inorganic film integrity, high hydrophilicity, and high proton conductivity, however, is exceedingly difficult to achieve in a single processing step.…”
mentioning
confidence: 99%
“…Thus, on the basis on 2-D NMR data, Janicke et al 11 have recently concluded that both four-and sixcoordinate Al centers can coexist in the inorganic walls. In any case, it seems clear that Al atoms in octahedral environments do not contribute to the Brønsted acidity.…”
mentioning
confidence: 99%
“…In our system, the amount of MG is not enough to justify the formation of a liquid crystal. Nevertheless, in the field of surfactant-templated mesostructured silica and aluminosilica materials, the formation of lyotropic hybrid organic/inorganic phases occurs both under a liquid crystal like approach (high concentration of surfactant) 21 and under dilute conditions, where self-organisation and precipitation is driven in solution by the cooperative formation of inorganic-organic interfaces, as proposed by Monnier et al 22 Chmelka and co. also reported on the formation of mesostructured aluminosilicate by the same approach and, interestingly, their advanced solid state NMR study showed that incorporation of aluminum in the inorganic framework did not induce a 29 Si chemical shift at -78 ppm, 23 which supports the fact that in our case the formation of a classical mesoporous aluminosilicate is most-likely excluded.…”
Section: Insights In the Reaction Mechanismsmentioning
confidence: 85%